Multi-element analysis of urine using octopole collision cell ICP-Q-MS - Patočka, Jan; Husáková, Lenka (University of Pardubice, 2020)
This study presents an octopole collision cell ICP-Q-MS methodology for interferencefree multi-element analysis of urine. The attention was paid to the performance of the 4th generation octopole-based collision cell in the Agilent 7900 Series ICP-MS in He-mode with kinetic energy discrimination (KED) for the elimination of polyatomic ions that are the main source of spectral interferences during the analysis of numerous elements, such as V, Cr, Fe, Co, Ni, Cu, As, Se, etc. However, collision mode using helium gas had the additional benefit of reducing the response for major matrix elements, thereby effectively raising the upper linear calibration range for these elements. Afterwards, the major elements could be determined in the same analytical run as the trace elements in the range of analytes typically reported in urine samples. The analysis was carried out after the initial 10-fold dilution of the urine samples and Rh was used as an internal standard to diminish non-spectral interferences originating from the sample matrix. Due to the excellent detection capability and practically no interferences, the method could be finally employed for analysis of 26 elements. Accuracy of the method was checked by the regular use of certified reference materials SeronormTM Trace Elements Urine Blank Lot OK4636 and SeronormTM Trace Elements Urine L-1 Lot 1011644, as well as by accurate isotope ratios measurements if possible.
Keywords: ICP-Q-MS; multi-element analysis of urine; interferences in ICP-MS